Strategi Peningkatan Kompetensi Asatidz dan Asatidzah Al-Qur’an dalam Pembelajaran Tahfidz Qur’an Menyongsong Revolusi Industri 5.0 - Heny Kusmawati (EL-TARBAWI, 2019)
Islam is one of the religions of rahmatan lil alamin and religion that are able to shape the human being as khalifah fil ard. This is in line with the 5.0 industrial revolution that is being adopted by the Japanese State where the human society is the basis of the development of the industrial revolution. Under the industrial revolution 4.0 the teacher already has problems about technological development. In Islam, it is highly recommended to be able to master technology. The one of problem for teacher comptence is when technology becomes a reason for someone not yet willing to memorize. At least the output of the quran generation is capable of being an attorney and an attorney according to the times. This paper discusses the improvement of original and authentic competencies in emptying the 5.0 industrial revolution. Efforts to improve original competence and respect are carried out by conducting training, kyai leadership or managerial services in accordance with the era, boarding facilities complete with the latest technology, enhancement of Continuing Professionalism and lesson study with the support of e-literacy, and regulations on authentic and independent competence standards in Indonesia.